Annular Pancreas Associated with TORCH-infection - S.V. Vesiolyi; R.P. Klimanskyi; K.V. Latyshov (Zaslavsky O.Yu., 2015)
The article presents follow-up in a newborn child with a congenital malformation of the gastrointestinal tract (annular pancreas), III degree prematurity against the background of persistent cytomegalovirus and toxoplasmosis infections. A successful surgical correction of malformation of the gastrointestinal tract has been made. Follow-up observation has shown a favorable outcome.